No, prime minister: explaining the House of Commons' vote on intervention in Syria. Issue 1 (2nd January 2016) - Kaarbo, Juliet; Kenealy, Daniel
ABSTRACT: On 29 August 2013, the UK House of Commons inflicted the first defeat on a Prime Minister over a matter of war and peace since 1782. Recalled to debate and vote on UK intervention in Syria, the Commons humbled the government and crucially impacted the development of UK foreign policy. This article places that vote, and the developments leading to it, in the context of the role of parliaments in security policy and explores the relationships between parliamentary influence, leadership, intra-party and intra-coalition politics, and public opinion. From an in-depth analysis of leaders' statements and parliamentary debate, we find a combination of intra-party politics and party leadership were most significant. An additional factor – the role of historical precedent – was also important. Our analysis explores the fluidity and interconnectedness of the various factors for parliamentary influence in foreign policy and offers directions for future theoretical development and empirical research.